Can recurrent cesarean section due to arrest of descent be predicted by newborn weight difference?. (February 2020) - Kugelman, Nir; Sagi-Dain, Lena; Kleifeld, Shiran; Kedar, Reuven; Bardicef, Mordehai; Toledano-Hacohen, Mirit; Damti, Amit
Abstract: Objective: To evaluate if newborn weight difference is associated with the mode of delivery in women with a previous cesarean section due to arrest of descent. Study Design: This retrospective cohort analysis included all women admitted to the delivery room of Carmel Medical Center with a singleton fetus at vertex presentation and a prior cesarean section for arrest of descent. A comparison was made between women who had a subsequent successful vaginal birth after cesarean delivery vs. a repeat cesarean section for arrest of descent. The primary outcome was newborn weight difference between the previous cesarean section and the present delivery. Secondary outcomes were gestational age, gravidity, age, induction of labor, previous vaginal birth and epidural analgesia. Results: Of 179 women with a prior cesarean section due to arrest of descent, 55 women (30.7 %) underwent an elective repeat cesarean section. Of the remaining 124 women, 95 women (76.6 %) achieved a vaginal delivery. Out of the 29 cases who underwent a repeat cesarean section, 18 women had a cesarean section for arrest of descent. Women who achieved vaginal delivery were more likely to be with higher gravidity, a previous vaginal delivery and a lower rate of epidural anesthesia. Following multivariate logistic regression, the women who required a cesarean section due to arrest of descent, had significantly higher birth weight in the current than in the previous pregnancy, compared to women achieving vaginal delivery (Odds Ratio 4.7, CI 95 % 1.4–15.7, P = 0.012). Conclusion: Current birth weight higher than the previous newborn weight in a cesarean section for arrest of descent is associated with lower likelihood of successful vaginal birth after cesarean delivery and therefore should be taken in consideration during fetal weight estimation and the decision on the mode of delivery. This issue should be explored in future prospective large-cohort studies.